Cervical Spine Dysfunction Following Pediatric Sports-Related Head Trauma. Issue 2 (March 2019) - Ellis, Michael J.; McDonald, Patrick J.; Olson, Ashley; Koenig, James; Russell, Kelly
Abstract : Objective: To examine the prevalence of cervical spine injuries among children and adolescents referred with suspected and diagnosed sports-related concussion (SRC); and evaluate the effect of cervical spine dysfunction (CSD) on physician-documented clinical recovery following SRC. Setting: A multidisciplinary pediatric concussion program. Participants: A total of 266 patients (6-19 years) referred with suspected SRC. Design: A retrospective cohort study. Main Measures: CSD defined as neurological symptoms localized to the cervical spine or the presence of neck pain, headache, or dizziness and abnormal cervical spine examination findings; physician-documented clinical recovery. Results: One patient was diagnosed with a T1 compression fracture. Of the 246 patients diagnosed with SRC, 80 (32.5%) met the clinical criteria for CSD including 4 patients with central cord neuropraxia and 1 with a spinal cord injury without radiographic abnormality (SCIWORA). Excluding patients with central cord neuropraxia OR SCIWORA, patients with SRC with CSD took longer to achieve physician-documented clinical recovery (28.5 days vs 17 days, P < .0001) and were 3.95 times more likely to experience delayed physician-documented clinical recovery (>4 weeks postinjury) compared with those without CSD. Conclusions: Patients with suspected and diagnosed SRC can present with a wide spectrum of coincident cervical spine injuries. Cervical spine dysfunction may be a risk factor for delayed clinical recovery.